2015
DOI: 10.3171/2014.11.jns142278
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral contrast-enhancing pontomedullary lesion due to an intracranial dural arteriovenous fistula with perimedullary spinal venous drainage: the exception that proves the rule

Abstract: Dural arteriovenous fistulas (DAVFs) are abnormal communications between dural arteries and dural venous sinuses, meningeal veins, or cortical veins. They account for 10%-15% of intracranial arteriovenous malformations.12,33 Grading of DAVF is based on the venous drainage pattern according to the classification schemes of Borden et al. and Cognard et al. 4,8 Venous cortical or perimedullary drainage and dilation are the hallmarks of high-grade DAVF and strongly correlate with increased risk of intracranial he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…5 The presentation and symptoms are often mistaken for other diagnoses, such as spinal stenosis, infarct, tumor, Guillain-Barré syndrome, or multiple sclerosis, although improved access to MRI and angiography have allowed for better detection and management. Roelz et al 9 recently reviewed MRI findings in 58 patients who presented with a Type V dAVF. Seventy-three percent of patients had central medullary edema on MRI, and 76% had T2 flow voids typical of engorged perimedullary veins.…”
Section: Diagnosis Of Cognard Type V Davfsmentioning
confidence: 99%
“…5 The presentation and symptoms are often mistaken for other diagnoses, such as spinal stenosis, infarct, tumor, Guillain-Barré syndrome, or multiple sclerosis, although improved access to MRI and angiography have allowed for better detection and management. Roelz et al 9 recently reviewed MRI findings in 58 patients who presented with a Type V dAVF. Seventy-three percent of patients had central medullary edema on MRI, and 76% had T2 flow voids typical of engorged perimedullary veins.…”
Section: Diagnosis Of Cognard Type V Davfsmentioning
confidence: 99%
“…4 With contrast-enhanced imaging, the detection rate of atypical perimedullary vessels increases to 76% but is often subtle. 5 Use of MRA increases the detection rate to 85%. 5 Four of our 5 patients (80%) retrospectively demonstrated atypical perimedullary vessels or flow voids on initial MR imaging, subtle in some instances.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, improper management and, in some reported instances, biopsy for a suspected neoplasm may occur. 5 We report a series of 5 patients who presented at 2 nearby academic institutions from 2012 to 2016 with DAVFs demonstrating medullary edema and enhancement at initial imaging. Most interesting, the unique pattern of edema was nearly identical in all 5 cases and, retrospectively, has been anecdotally mentioned previously.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The laboratory studies revealed a slightly elevated fast- A carotid and transcranial duplex sonographic study 8,13 . Including the patients mentioned here, only 6 patients with an isolated unilateral brainstem lesion due to DAVF have been reported in studies in the English language literature 6,8,13,14,16 . A summary of these 6 cases is presented in Table 1.…”
Section: Case Presentationmentioning
confidence: 99%